Id1 and Id3 co-expression correlates with clinical outcome in stage III-N2 non-small cell lung cancer patients treated with definitive chemoradiotherapy - Castañon Eduardo; Bosch-Barrera Joaquim; López Inés; Collado Víctor; Moreno Marta; López-Picazo José María; Arbea Leire; Lozano María Dolores; Calvo Alfonso; Gil-Bazo Ignacio (Journal of Translational Medicine, 2013)
Background Inhibitor of DNA binding 1 (Id1) and 3 (Id3) genes have been related with the inhibition of cell differentiation, cell growth promotion and tumor metastasis. Recently, Id1 has been identified as an independent prognostic factor in patients with lung adenocarcinoma, regardless of the stage. Furthermore, Id1 may confer resistance to treatment (both, radiotherapy and chemotherapy). Methods We have studied, using monoclonal antibodies for immunohistochemistry, the Id1 and Id3 tumor epithelial expression in 17 patients with stage III-N2 non-small cell lung cancer (NSCLC) treated with definitive chemoradiotherapy. Results Id1 expression is observed in 82.4% of the tumors, whereas Id3 expression is present in 41.2% of the samples. Interestingly, Id1 and Id3 expression are mutually correlated (R = 0.579, p = 0.015). In a subgroup analysis of patients with the most locally advanced disease (T4N2 stage), co-expression of Id1 and Id3 showed to be related with a worse overall survival (45 vs 6 months, p = 0.002). A trend towards significance for a worse progression free survival (30 vs 1 months, p = 0.219) and a lower response rate to the treatment (RR = 50% vs 87.5%, p = 0.07) were also observed. Conclusions A correlation between Id1 and Id3 protein expression is observed. Id1 and Id3 co-expression seems associated with a poor clinical outcome in patients with locally advanced NSCLC treated with definitive chemoradiotherapy.